Novel laparoscopic “lateral three-port technique” of extended totally extra peritoneal approach for ventral hernias: Short-term results and technical aspects of 100 consecutive cases from a single center - K. Ganesh Shenoy; Marina Thomas; Ramesh B S; Amol Siddalingappa Jeur; Nawab Jan (International Journal of Abdominal Wall and Hernia Surgery)
OBJECTIVES: The purpose of this study was to develop a simplified technical modification with an attempt to standardize the extended totally view extraperitoneal–Rives Stoppa (ETEP-RS) procedure. In this article, we present the technical aspects to perform this procedure by using novel lateral three ports and the short-term results of our experience in this subset of patients. MATERIALS AND METHODS: A retrospective analysis of 100 consecutive patients who underwent laparoscopic ETEP-RS using the lateral three-port technique between January 2022 and July 2023 was done. In this technique, three lateral ports were placed for both midline and lateral ventral hernias (VH), with no need to shift camera, working ports, and monitor positions throughout the procedure. It can be coupled with repair of associated right inguinal hernia, divarication of recti (DR), and transversus abdominis release (TAR). RESULTS: Of 100 consecutive patients who underwent ETEP approach for VH by using our lateral three-port technique, 84 patients underwent ETEP-RS and 16 patients underwent ETEP-TAR. Out of these 100 patients, 4 patients underwent ETEP for associated right inguinal hernia. The mean operating time was 119.9 min with a range from 45 min to 185 min. The mean defect width was 7.24 cm. We used 20 cm × 15 cm medium weight polypropylene mesh for most of our patients. There were no recurrences in the follow-up period. One patient required laparoscopic re-exploration for posterior rectus sheath rupture. CONCLUSION: The laparoscopic novel lateral three-port ETEP-RS technique is safe, feasible, cost-effective, and reproducible. This can be combined with right-sided TAR, right inguinal hernias, and repair of DR. It can be standardized; however, larger studies and longer follow-up are needed to have an evidence-based answer.